Antibiofilm properties of Clitoria ternatea flower anthocyanin-rich fraction towards Pseudomonas aeruginosa. Issue 4 (26th April 2022) - Jeyaraj, Ethel Jeyaseela; Nathan, Sheila; Lim, Yau Yan; Choo, Wee Sim
Abstract : In Asia, Clitoria ternatea flowers are commonly used as a traditional medicinal herb and as a food colourant. Their bioactive compounds have anti-inflammatory, anti-microbial and anti-biofilm activities. Pseudomonas aeruginosa is one of the major pathogens that cause biofilm-associated infections resulting in an increase in antimicrobial resistance. Hence, the aim of this study was to investigate if the anti-biofilm properties of the anthocyanin-rich fraction of C. ternatea flowers were effective against P. aeruginosa . The effect of the anthocyanin-rich fraction of C. ternatea flowers on P. aeruginosa biofilms formed on a polystyrene surface was determined using the crystal violet assay and scanning electron microscopy (SEM). The anthocyanin-rich fraction reduced biofilm formation by four P. aeruginosa strains with a minimum biofilm inhibitory concentration value ranging between 0.625 and 5.0 mg ml −1 . We further show that the biofilm-inhibiting activity of C. ternatea flowers is not due to the flavonols but is instead attributed to the anthocyanins, which had significant biofilm inhibitory activity (64.0±1.1 %) at 24 h in a time–response study. The anthocyanin-rich fraction also significantly reduced bacterial attachment on the polystyrene by 1.1 log c.f.u. cm −2 surface based on SEM analysis. Hence, anthocyanins from C. ternatea flowers have potential as an agent to decrease the risk of biofilm-associated infections.